Ecological and economic differentiation of the urbanized territory of the regions of Kazakhstan - Kabdybay, A.K.; Kenzhebekov, N.D.; Daniyarova, M.T. (BUKETOV BUSINESS REVIEW, 2019)
In this article a methodology of ecological and economic differentiation of cities of Kazakhstan is presented. Application of this method allows us to estimate the environmental impact on urban areas in the point system and classify them according to the degree of environmental impact. An ecological and economic differentiation of cities of Kazakhstan is conducted. The features of the structure of the urban area are examined, in which the main part is urban agglomeration. The advantages applying zoning of urban area are defined, also disadvantages and disruption of zoning principles are presented resulting to structural imbalance of urban agglomeration. The problem of the transformation of the functional structure of the urbanized territory is highlighted. The features of cities of Kazakhstan are identified due to the geography and history of the country, which must be taken into account in environmental and economic differentiation. The presented research methodology is based on 23 criteria, grouped into 3 main categories. The main risks impact on urbanization processes in Kazakhstan is revealed. The main types of environmental risks in urban areas are identified. An assessment of the environmental risks of Karaganda is realized. An ecological and economic differentiation of urban areas and cities of Kazakhstan is conducted.